DEVELOPMENT OF PROFESSIONAL COMPETENCY IN PRESCHOOL TEACHERS - Mamatova, Dilnoza (Журнал иностранных языков и лингвистики, 2021)
Currently, attention is paid to the development of the pre-school education system in our country, a modern system is being created on the basis of the most advanced foreign experience. Research is being carried out on the content of the pre –school education system and the creation of the most necessary framework of its implementation using modern pedagogical and information and communication technologies. These studies are mainly aimed at the formation and improvement of the content of pre-school education pedagogy, training of mature qualified pedagogical personnel and training of specialists in accordance with the modern requirements and improving their skills. In this article, some concepts and opinions of our scientists on the topic of development of professional competence of pedagogical workers of preschool organizations are discussed on the basis of authorship. Pedagogical skill develops and improves in the process of the work of each pedagogical employee, which, of course, depends on the work of a specialist educator on himself.